Relationship between TQM dimensions and organizational performance - Shahid Mehmood; Faisal Qadeer; Aftab Ahmad (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The maintenance and enhancement of organizational performance is a challenge for firms as they always try to sustain competitive advantage. This challenge may be convened through the principles of total quality management (TQM). The organizations ought to understand what dimensions of quality management system are more important for performance enhancement. This paper focuses on four TQM dimensions; customer focus, continuous improvement, employee involvement, top management support to identify the most critical quality dimensions as predictor of organizational performance. The results are based on the empirical data collected from a self-administrative survey from 90 organizations (270 managers) of textile sector in Pakistan. Multiple linear regression results reveal that continuous improvement and employee involvement are the most critical dimensions for predicting organizational performance. Whereas, customer focus and top management support has no statistical significance for predicting the performance. The research poses future directions along with implications for theory and practitioners.
Keywords: 330; TQM dimensions; organizational performance; textile sector; Pakistan